Cultural Semiotic Analysis of the Transformation of the “Hayu” Batik Motif from Royal Tomb Ornaments - Sahid Teguh, Widodo (Proceeding of International Joint Conference on UNESA, 2025)
The Hayu batik motif is a contemporary batik design developed since 2022 by researchers from the University Centre of Excellence Javanologi for Javanese Traditions, Universitas Sebelas Maret, in collaboration with traditional batik artisans on the slopes of Mount Lawu, Karanganyar, Central Java. A distinctive feature of this motif lies in its adaptation of aesthetic elements from the ancient royal tombs of Pura Mangkunegaran, Surakarta. This study aims to examine the progress achieved to date and to explore the “behind-the-layers” transformation process through which the aesthetic elements of royal tombs are reinterpreted into batik design elements. Specifically, the objectives are: (1) to explain the transformation of forms from the aesthetic elements of ancient tombs into the elegant design patterns of the Hayu batik, and (2) to analyze the aesthetic transformation process that adapts traditional aesthetic values to the needs and tastes of modern society, resulting in a synthesized Hayu batik pattern. Both are expected to illuminate the shift from the sacred imagery of heritage to a more profane, accessible, and contemporary form aligned with current trends. Employing a cultural semiotic approach, this qualitative exploratory research interprets systems of symbols, signs, and codes, particularly regarding the transformation of symbolic meaning and cultural expression. The findings reveal that form transformation is achieved through translation, rotation, reflection, and dilation. Where translation involves subtractive, additive, dimensional, and geometric transformations while aesthetic transformation encompasses changes in medium (stone to fabric), atmosphere of appreciation, design orientation, and lifestyle. This study also presents the creation process and philosophical values of the four Hayu motif designs, positioning Hayu as an innovative breakthrough in batik art that integrates historical narratives, events, and connections into new symbols and imaginative-practical aesthetic expressions.